POEMS syndrome as an uncommon cause of papilledema - Franco, Carlos Mario; Balparda, Kepa; Díaz, Ana María; Jiménez, Daniel; Pamplona, Ana Paulina (Nepalese Journal of Ophthalmology, 2014)
Background: Polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, and skin changes (POEMS) syndrome is an uncommon condition related to a paraneoplastic syndrome secondary to an underlying plasma cell disorder. Among the myriad of manifestations of the disease, ocular signs and symptoms are relatively prevalent, affecting about half of all patients with the disease. Objective: To report the ocular manifestations of POEMS syndrome. Case: A 47-year-old lady diagnosed to have POEMS syndrome presented with painless progressive visual diminution. Her color vision was impaired. There was bilateral papilloedema. Conclusion: POEMS syndrome should be considered among the differential diagnoses of all patients with a bilateral papilledema in which no other cause can be readily elucidated. DOI: http://dx.doi.org/10.3126/nepjoph.v6i1.10781 Nepal J Ophthalmol 2014; 6 (2): 105-108